Calidad de atención y satisfacción de los usuarios de la municipalidad distrito de San Juan Bautista 2021 - Torres Casimiro, Milagros (2022)
The objective of this research was to determine the relationship between the quality of care and the satisfaction of the users of the Municipality of the District of San Juan in the period 2021. Therefore, it was a descriptive and correlational research, developed under a non-specific design. experimental. As a population, I take the entire citizenry, that is, 1 452 users, from which a sample of 294 people has been drawn. For data collection it was necessary to use the survey technique, data that were recorded through a questionnaire for each of the variables. The research work concluded that the relationship (rho = 0.852; p = 0.000) is significant between the quality of care and user satisfaction; Similarly, the dimensions of service processes (rho = 0.769), human resources (rho = 0.747), reliability (rho = 0.713), security (rho = 0.693), empathy (rho = 0.778) and infrastructure (rho = 0.775), present a significant (p = 0.000) and considerable relationship with user satisfaction.